An Improved Procedure for the Preparation of Thrombin Low Molecular Weight Substrates - Peptide p-Nitroanilides - Chistov, A.A; Talanova, A.V.; Melnikova, M.V.; Kuznetsova, S.S.; Kolesanova, E.F. (Biomedical Chemistry: Research and Methods, 2018)
Low molecular weight chromogenic thrombin peptide substrates, p-nitroanilides of short peptides protected at their N-terminal amino group, were prepared by solid-phase peptide synthesis on polystyrene-divinylbenzene polymer with trityl groups with preliminary attached p-phenylene diamine moiety. After the cleavage from the resin peptide p-aminoanilides were mildly oxidized to p-nitroanilides with the mixture of potassium sulfate and persulfate. Adsorption onto polymer support Bio-Beads SM-2 with further elution by acetonitrile allowed easy separating peptide p-nitroanilides from the oxidizer and obtaining the thrombin chromogenic substrate preparations with the target substance contents of not less than 95% and yields of 30-40%. Thrombin effectively catalyzed hydrolysis of the prepared substrates with KM and Vmax values of 29-134 mM and 0.03-1/16 mM/s, respectively.